In Vitro Selective Growth-Inhibitory Effect of 8-Hydroxyquinoline on Clostridium perfringens versus Bifidobacteria in a Medium Containing Chicken Ileal Digesta - Skrivanova, Eva; Van Immerseel, Filip; Hovorkova, Petra; Kokoska, Ladislav (PloS one, 2016)
Clostridium perfringens-induced necrotic enteritis is generally controlled by antibiotics. However, because of increasing antibiotic resistance, other antibacterial agents are required, preferably ones that do not affect the beneficial intestinal microbiota of the host. This study evaluated the in vitro selective growth-inhibitory effect of 8-hydroxyquinoline (8HQ) on C. perfringens vs. bifidobacteria in a medium containing chicken ileal digesta. Prior to the experiments, the minimum inhibitory concentrations of 8HQ and penicillin G were determined by broth microdilution assay. The minimum inhibitory concentration values of 8HQ for C. perfringens were 16-32 times lower than the values for bifidobacteria. Treatment of autoclaved and non-autoclaved chicken ileal digesta with 8HQ showed a selective anticlostridial effect. After incubation of C. perfringens with autoclaved ileal digesta for 3 h, all 8HQ concentrations tested (32-2048 μg/mL) significantly reduced C. perfringens bacterial count. In contrast, the same treatment had no or only a slight effect on bifidobacteria counts. Unlike 8HQ, penicillin G did not exhibit any selectivity. Similar results were obtained after incubation for 24 h. In non-autoclaved ileal digesta, all 8HQ concentrations tested significantly reduced C. perfringens bacterial counts after incubation for 30 min and 3 h, while no effect was observed on bifidobacteria. These results suggest that 8HQ may serve as a prospective veterinary compound for use against necrotic enteritis in poultry.
Keywords: nemoci drůbeže; Clostridium Infections; Bifidobacterium; Chickens; zvířata; klostridiové infekce; Anti-Bacterial Agents; Oxyquinoline; oxychinolin; Ileum; Poultry Diseases; Clostridium perfringens; ileum; kur domácí; antibakteriální látky; Animals